Sensitivity characteristics of high-birefringence Sagnac interferometer sensors - Zu, Peng (2013)
The sensitivity characteristics of the sensors based on high-birefringence Sagnac interferometer are theoretically analyzed and experimentally verified. We analyze the sensitivity of the sensor in terms of the frequency instead of the wavelength of the light and the sensitivity can be improved by reducing the length of high birefringence fiber. The strain sensing experiments are carried out and the experimental results agree well with the theoretical analysis.